Estratégias para a determinação de minoxidil - Sousa, Rogério Adelino de (Universidade Federal de São Carlos, 2005)
Methods for the determination of minoxidil in commercial samples are presented. The minoxidil is a pharmaceutical whose dilation blood vessel property is used in the treatment of the Arterial Hypertension and in the treatment of the Alopecia Areata. Two commercial samples were analyzed, the Regaine® (Pharmacia, U.S.A.) and the Neoxidil® (Galderma, Brazil) both are solutions of topical use containing 2% of minoxidil (20 mg mL-1) in a mixture of ethanol and propilenoglicol as vehicle. Four proposals for the determination of minoxidil in commercial samples were considered. The first one was the titrimetric determination of minoxidil in pharmaceutical formulations using potassium permanganate in which it was possible to quantify the amount of minoxidil in the commercial samples by classical titration. In other method it was used a spectrophotometric titration for the determination of minoxidil in pharmaceutical formulations using potassium permanganate, in which the decrease in the absorbance at 550 nm. The third method was the use of the flow injection analysis (FIA) for the determination of minoxidil in pharmaceutical formulations using potassium permanganate as redox reagent, in which the decrease of the absorbance of the carrying potassium permanganate solution in acidic media was monitored spectrophotometricaly at 550 nm under controlled temperature at 50 OC. Finally it was considered a method that consists in a potenciometric titration of minoxidil with potassium dichromate, in which the potential difference between is monitored a platinum electrode (working) and a saturated calomel electrode (reference) at 60 OC.
Strategy for the determination the minoxil
Keywords: Química analítica; Minoxidil; Titulação; FIA (Flow Injection Analysis); Permanganato de potássio; Dicromato de potássio; CIENCIAS EXATAS E DA TERRA::QUIMICA